1996
DOI: 10.1029/96wr00291
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mass transfer characteristics and porous media heterogeneity on nonaqueous phase dissolution

Abstract: A two‐dimensional multiphase flow and species transport model was developed and applied to the case of nonaqueous phase liquid (NAPL) emplacement and dissolution in both homogeneous and heterogeneous porous media systems. Simulations were performed to observe dissolution rate variations and the degree of NAPL‐aqueous phase nonequilibrium as a function of two aqueous phase velocities and five forms of the NAPL‐aqueous phase mass transfer formulation. An integrated form of the Damkohler number was introduced to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 69 publications
(51 reference statements)
2
81
0
4
Order By: Relevance
“…Several theoretical and experimental studies have shown that the aqueous-phase concentrations of dissolved oil can be significantly lower than equilibrium conditions for relatively large entrapped NAPL ganglia, high groundwater velocities, or low NAPL saturations [e.g., Mayer and Miller 1996]. These studies often yield formulations for mass transfer 4.60 correlations between the NAPL and aqueous phases, that relate the mass transfer coefficient, in dimensionless form as the Sherwood number Sh, to other system properties.…”
Section: Kinetic Dissolution/solubilization Of Oilmentioning
confidence: 99%
“…Several theoretical and experimental studies have shown that the aqueous-phase concentrations of dissolved oil can be significantly lower than equilibrium conditions for relatively large entrapped NAPL ganglia, high groundwater velocities, or low NAPL saturations [e.g., Mayer and Miller 1996]. These studies often yield formulations for mass transfer 4.60 correlations between the NAPL and aqueous phases, that relate the mass transfer coefficient, in dimensionless form as the Sherwood number Sh, to other system properties.…”
Section: Kinetic Dissolution/solubilization Of Oilmentioning
confidence: 99%
“…The impact of subsurface heterogeneity and non-uniform immiscibleliquid distribution on mass-removal behavior and associated aqueous-phase concentrations (mass flux) has been examined for some time through laboratory, modeling, and field studies (e.g., Schwille, 1988;Dorgarten, 1989;Guiguer, 1991;Anderson et al, 1992;Brusseau, 1992;Guarnaccia and Pinder, 1992;Mayer and Miller, 1996;Berglund, 1997;Nelson and Brusseau, 1997;Blue et al, 1998;Powers et al, 1998;Unger et al 1998;Broholm et al, 1999;Brusseau et al, 1999;Frind et al, 1999;Zhang and Brusseau, 1999;Brusseau et al, 2000;Nambi and Powers, 2000;Saba and Illangasekare, 2000;Zhu and Sykes, 2000;Rivett et al, 2001;Sale and McWhorter, 2001;Brusseau et al, 2002;Jayanti and Pope, 2004;Lemke et al, 2004;Parker and Park, 2004;Phelan et al, 2004;Soga et al, 2004;Falta et al, 2005;Jawitz et al, 2005;Rivett and Feenstra, 2005;Fure et al, 2006;Lemke and Abriola, 2006;Brusseau et al, 2007). An early effort to quantify the relationship between contaminant mass flux reduction and mass removal, and the resultant reduction in risk, was presented by Freeze and McWhorter (1997).…”
Section: Introductionmentioning
confidence: 99%
“…They observed Several researchers have recently used numerical models to predict NAPL dissolution in heterogeneous media described by random distributions of the hydraulic conductivity fields [Mayer and Miller, 1996;Dekker, 1996;Berglund, 1997]. In general, increases in the variance describing the distribution of hydraulic conductivities resulted in the increased time for remediation.…”
Section: Introductionmentioning
confidence: 99%
“…Application of these relationships [e.g., Miller et al, 1990; Powers et al, 1994a] often required an extrapolation to NAPL saturations much higher than the values used in their development. Mayer and Miller [1996] noted that small differences among the various relations describing mass transfer coefficients developed from experiments with homogeneous media resulted in more significant differences in predicted aqueous phase concentrations when applied to heterogeneous systems.…”
Section: Introductionmentioning
confidence: 99%